KEBIJAKAN INDONESIA TERHADAP IMIGRAN ILEGAL DAN HUBUNGANNYA DENGAN KEDAULATAN NEGARA - Eva Johan (Yuridika, 2013)
Many illegal migrants are preferring to enter Indonesia before they go to Australia. In order to tackle the arrival of those illegal migrants, Australian government enforces Third Country's policy and ban the illegal migrants by sending them back to Indonesian water. As sovereign state does Indonesia has an effective policy to handle these issues? This research applies juridical normative approach using primary and secondary data, studying and evaluating such law principles and relevant laws. This research concludes that through Act No.6 Year 2011 on Imigration, Indonesia deals with ineffective and partial by putting illegal migrant as victim rather than smuggler. As the policy considers them as victims, there are no sanctions and deterrent effects. Indonesia shall apply the Principle of State Sovereignty for basic guidance to make policy concerning illegal migrant.